Maps for analysis of nonlinear dynamics - Kaulakys, Bronislovas (Nonlinear Analysis: Modelling and Control, 1998)
Area preserving maps provide the simplest and most accurate means to visualize and quantify the behavior of nonlinear systems. Convenience of the mapping equations of motion for investigation of transition to chaotic behavior in dynamics of classical atom in microwave field, transition to nonchaotic behavior in randomly driven systems and induced quantum dynamics of simple and multilevel systems is demonstrated.
Keywords: none